Indonesia's Geopolitical and Economic Projections Amidst Quad Dynamics in the Indo-Pacific - Budiman, Bedi; Hutama, M Rizky Ganda; Abdullah, Siti Intan Nordiana Wong (International Journal of Economics Development Research (IJEDR), 2025)
This research aims to analyse Indonesia's geopolitical and economic projections amid the dynamics of competition between China and the Quad in the Indo-Pacific region. Indonesia, as a strategically positioned country at the heart of the Indo-Pacific region, has an important role in maintaining regional stability and security, as well as maximising its national interests. Through bandwagoning and hedging plus approaches, Indonesia has managed to maintain a strong economic relationship with China, while maintaining a balance with the Quad countries focusing on freedom of navigation and maritime security issues. While Indonesia's relationship with China provides significant economic benefits, this strategy should be balanced with maritime defence capacity building and alliance diversification to reduce economic dependence. The research also highlights the importance of maintaining ASEAN centrality in the face of global tensions and encouraging inclusive diplomacy at the regional level. The results show that Indonesia can play a role as a regional leader that maintains regional stability, as well as capitalise on economic opportunities without getting caught up in the geopolitical polarisation between China and the Quad. This research provides Indonesia's foreign policy recommendations to strengthen maritime diplomacy, enhance economic cooperation, and expand alliance diversification to ensure maritime sovereignty and stability of the Indo-Pacific region.